Experiences of accessing maternal health care services in a rural community of South Africa - Tapera, Lennox (University of the Free State, 2020)
Access to maternal health care is a global concern, especially for developing countries. South Africa's health system faces numerous challenges and poor access to maternal health care services (MHS) is a major contributor to maternal deaths nationwide. Maternal health entails social and medical health care services rendered to both mother and child during pregnancy, at childbirth and after delivery. Few studies have been conducted on experiences of women in accessing maternal health care in rural areas. Therefore, this study aimed at exploring rural women's experiences in accessing MHS in Rethabiseng within the Tshwane Metropolitan Municipality. More specifically, the objectives of the study were to describe knowledge about maternal health care, to explore women's maternal health care needs, maternal health care seeking behaviour, the facilitators to accessing MHS, the barriers to accessing MHS and to suggest recommendations to improve access to maternal health services. The Social-Ecological Model guided the research, and women's experiences of accessing MHS were explored on each level from individual, interpersonal, community and organisational level.
Dissertation (MDS (Development Studies))--University of the Free State, 2020
Keywords: Maternal health care services (MHS); Maternal health; Maternal health care services (MHS) -- Rural women; Rural health care; Maternal death